GeV-scale accelerators driven by plasma-modulated pulses from kilohertz lasers - Jakobsson, O; Hooker, SM; Walczak, R (American Physical Society, 2021)
We describe a new approach for driving GeV-scale plasma accelerators with long laser pulses. We show that the temporal phase of a long, high-energy driving laser pulse can be modulated periodically by copropagating it with a low-amplitude plasma wave driven by a short, low-energy seed pulse. Compression of the modulated driver by a dispersive optic generates a train of short pulses suitable for resonantly driving a plasma accelerator. Modulation of the driver occurs via well-controlled linear processes, as confirmed by good agreement between particle-in-cell (PIC) simulations and an analytic model. PIC simulations demonstrate that a 1.7 J, 1 ps driver, and a 140 mJ, 40 fs seed pulse can accelerate electrons to energies of 0.65 GeV in a plasma channel with an axial density of 2.5 × 1017cm−3. This work opens a route to high repetition-rate, GeV-scale plasma accelerators driven by thin-disk lasers, which can provide joule-scale, picosecond-duration laser pulses at multikilohertz repetition rates and high wall-plug efficiencies.